Management of Pyrrosia Mirb. (Polypodiaceae) Fern Specimens in Herbarium Depokensis (UIDEP) Universitas Indonesia, Depok - Atria, Mega; Rahmandika, Ghifari; Salamah, Andi; Saifudin, Saifudin; Putrika, Afiatry (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2025)
AbstractThe herbarium harbors collections of preserved plants used for scientific purposes. It is important to keep information about plants in a valid herbarium collection. This study aims to establish a valid collection and database of Pyrrosia stored in Herbarium Depokensis (UIDEP) through herbarium management. The management process includes taxonomic validation, specimen revitalization, and digitization. Taxonomic validation results showed there were 3 species of Pyrrosia namely P. piloselloides, P. lanceolata, and P. longifolia. These three species can be distinguished by rhizome scales, the shape of the lamina, and soral position. Physical examination throughout specimens showed several problems including loose specimen parts and specimen damage due to insects. Almost all collections (49 out of 59 specimens) did not include fertile lamina which is an important identifying character in Pyrrosia. To complete the herbarium data, 10 new Pyrrosia samples were collected at Green Spaces (RTHK) in Universitas Indonesia. All valid data and pictures undergo a digitization process. Those digitized data were then uploaded to the Herbarium UIDEP website (ruangkoleksibiotaui.id). This resulted in a Pyrrosia database that can be widely accessed by the public.AbstrakHerbarium menyimpan koleksi tanaman yang diawetkan yang digunakan untuk tujuan ilmiah. Penting untuk menyimpan informasi tentang tanaman dalam koleksi herbarium yang valid. Penelitian ini bertujuan untuk membangun koleksi dan database valid Pyrrosia yang disimpan di Herbarium Depokensis (UIDEP) melalui pengelolaan herbarium. Proses pengelolaannya meliputi validasi taksonomi, revitalisasi spesimen, dan digitalisasi. Hasil validasi taksonomi Pyrrosia menunjukkan terdapat 3 spesies, yaitu P. piloselloides, P. lanceolata, dan P. longifolia. Ketiga spesies ini dapat dibedakan berdasarkan sisik rimpang, bentuk lamina, dan letak soral. Pemeriksaan fisik pada seluruh spesimen menunjukkan beberapa permasalahan antara lain bagian spesimen yang lepas dan kerusakan spesimen akibat serangga. Hampir semua koleksi (49 dari 59 spesimen) tidak mencantumkan lamina subur yang merupakan karakter pengidentifikasi penting pada Pyrrosia. Untuk melengkapi data herbarium, dilakukan pengumpulan 10 sampel Pyrrosia baru di Ruang Terbuka Hijau (RTHK) Universitas Indonesia. Semua data dan gambar yang valid menjalani proses digitalisasi. Data digital tersebut kemudian diunggah ke website Herbarium UIDEP (ruangkoleksibiotaui.id). Hal ini menghasilkan database Pyrrosia yang dapat diakses secara luas oleh masyarakat.